Aerodynamic Analysis Models for Vertical-Axis Wind Turbines - M. T. Brahimi; A. Allet; I. Paraschivoiu (International Journal of Rotating Machinery)
This work details the progress made in the development of aerodynamic models for studying Vertical-Axis Wind Turbines (VAWT's) with particular emphasis on the prediction of aerodynamic loads and rotor performance as well as dynamic stall simulations. The paper describes current effort and some important findings using streamtube models, 3-D viscous model, stochastic wind model and numerical simulation of the flow around the turbine blades. Comparison of the analytical results with available experimental data have shown good agreement.